2017
DOI: 10.3389/fped.2017.00136
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Venous Thromboembolism

Abstract: Neonates are the pediatric population at highest risk for development of venous thromboembolism (VTE), and the incidence of VTE in the neonatal population is increasing. This is especially true in the critically ill population. Several large studies indicate that the incidence of neonatal VTE is up almost threefold in the last two decades. Central lines, fluid fluctuations, sepsis, liver dysfunction, and inflammation contribute to the risk profile for VTE development in ill neonates. In addition, the neonatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 56 publications
1
45
0
8
Order By: Relevance
“…8 In contrast, a prospective study of neonates who underwent central venous catheter placement indicated a 13% incidence of CT, 9 while another evaluating only umbilical catheters revealed a higher incidence of 22%. 10,11 These studies taken together with our study suggest that neonates with catheters are at high risk for CT, but CTs are not always associated with clinically significant symptoms. This suggests that other factors must play an important role in those CT that become symptomatic.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…8 In contrast, a prospective study of neonates who underwent central venous catheter placement indicated a 13% incidence of CT, 9 while another evaluating only umbilical catheters revealed a higher incidence of 22%. 10,11 These studies taken together with our study suggest that neonates with catheters are at high risk for CT, but CTs are not always associated with clinically significant symptoms. This suggests that other factors must play an important role in those CT that become symptomatic.…”
Section: Discussionsupporting
confidence: 56%
“…A recent review identified that the distribution of venous thromboembolism across the pediatric age group is bimodal, with one spike in the neonatal period and a second spike in the adolescent period. 11 Age has been positively associated with thrombosis in critically ill patients in the pediatric intensive care unit, where children older than 13 years were significantly more likely to develop CT compared with infants younger than 1 year. 22 A systematic review of several adult population-based studies found that older age was significantly associated with catheter-related thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging/angiography, abdominal computerized tomography (CT), and echocardiography were employed to detect IVC thrombi in five cases, and in two cases the diagnosis was established at postmortem . Although gray‐scale/Doppler ultrasonography is recognized as the modality of choice in suspected neonatal IVC thrombosis, CT provides more detailed information about thrombus extension, but at the expense of radiation exposure . In our review, 75% ( n = 46/61) of the cases were diagnosed by ultrasound alone, while 7% ( n = 4/61) were diagnosed by ultrasound with CT confirmation.…”
Section: Resultsmentioning
confidence: 94%
“…15,22 Although gray-scale/Doppler ultrasonography is recognized as the modality of choice in suspected neonatal IVC thrombosis, CT provides more detailed information about thrombus extension, but at the expense of radiation exposure. 61 In our review, 75%…”
Section: Diagnosis Of Ivcsmentioning
confidence: 80%
“…The Virchow's Triad proposes that VTE occurs as a result of blood stasis, vascular endothelial injury and inherited or acquired hypercoaguable states. 2 Keeping in view the pathophysiology of VTE, the patients after surgery are at higher risk of VTE because surgery induces inflammatory responses and hypercoagulable state along with endothelial injury. After surgery limited movements result in venous stasis.…”
Section: Introductionmentioning
confidence: 99%